La guerra disegnata: La mappa di Strigonia di Claudio Cogorano del 1595 nei documenti archivistici modenesi e fiorentini - Lupoli, Rosa (Verbum – Analecta Neolatina, 2017)
This paper presents the study of a beautiful map of the city of Esztergom (Strigonia in Latin) from the 16th century. The map, which is anonymous and without date, is conserved in the State Archive of Modena (Italy). Through the comparison of archival collections from Modena and Florence, it is possible to attribute the document to the engineer Claudio Cogorano (1554–1618) from Parma, a renown designer of military fortifications in the 16th century, active in Hungary during the epoch of the Ottoman–Habsburg wars (1594–1596). The documents presented in this paper record his work in the entourage of Don Giovanni de Medici, famous warlord of the Medici family, and trace back to the years 1595–1596 during which they collaborated to the project of the fortress of Komárom (Comar) and Esztergom. These documents allow us to attribute to Claudio Cogorano the paternity of some important Hungarian maps of that time in the Archive of Modena.